Penggunaan Metode Poster Coment untuk Meningkatkan Hasil Belajar IPA Materi Perubahan Lingkungan Siswa Kelas IV SD Negeri 012 Koto Kari - Hermida, Hermida (GERAM: Gerakan Aktif Menulis, 2017)
The application of learning model, methode, and the technique in every learning process would create the better atmosphere in classroom and students’ activity. One of the methods that could be used was Poster Comment Method. This method was used in Classrom Action Research with the subject was Science and the material was Environmental Change in grade IV SDN 012 Koto Kari. The purpose of this research was to represent how the learning result improved as the Poster Comment Method was applied in Science with the material was Environmental Change in grade IV SDN 012 Koto Kari. This research used four steps of Classroom Action Research; planning, proceeding, observing, and reflecting. One cycle consisted those four steps while the research was done in two cycles. The result showed in beginning data, there were only 9 students passed or 47%. After the treatment was given, in cycle 1 it showed that 15 students or 78% students passed, and finally in the second cycle the data increased to be 18 students or 95% students passed out of 18 students.